Women's international thought : a new history - Owens, Patricia, 1975- 1975- Herausgeber; Rietzler, Katharina 1978- Herausgeber (Cambridge University Press, 2021)
Women's International Thought: A New History is the first cross-disciplinary history of women's international thought. Bringing together some of the foremost historians and scholars of international relations working today, this book recovers and analyses the path-breaking work of eighteen leading thinkers of international politics from the early to mid-twentieth century. Recovering and analyzing this important work, the essays offer revisionist accounts of IR's intellectual and disciplinary history and expand the locations, genres, and practices of international thinking. Systematically structured, and focusing in particular on Black diasporic, Anglo-American, and European historical women, it does more than 'add women' to the existing intellectual and disciplinary histories from which they were erased. Instead, it raises fundamental questions about which kinds of subjects and what kind of thinking constitutes international thought, opening new vistas to scholars and students of international history and theory, intellectual history and women's and gender studies